Traditional House Lexical Items of the Batu Bara Malay: An Ecolinguistics Study - Harry Sambayu; Amrin Saragih; Sumarsih Sumarsih (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study investigated the maintainability of the traditional lexical housing of Batu Bara Malay. This study was kind of ecolinguistics. It was run by applying qualitative research methodology. The finding of this study total number lexical items related to housing in Batu Bara Malay are 210 lexical items. The lexical item is divided into 5 (five) classification. They are Top Parts, there are 37 lexical items consist of 21 items interior and 16 exteriors. Middle Parts, there are 55 lexical items consist of 45 items interior and 10 items exterior. Bottom Parts, there are 13 lexical items consist of 2 items interior and 11 items exterior. Outdoor Items, there are only consist of 27 items exterior, and Extended Items Related to Housing there are 78 items. The Most lexical items are the middle part among all classification. The least one is bottom parts. The new finding in this study, the use of lexical items related to house is at risk.